Social desirability in the selection process: new insights from a novel context. (28th May 2012) - Li, Andrew; Bagger, Jessica; Friske, Wesley
<x xml:space="preserve">Abstract</x> In this study we examined whether past research on social desirability based on western samples could be generalized to a novel environment, such as Singapore. We also investigated whether cultural orientations predict the inflation of personality scores in the selection process and whether they influence the effectiveness of social desirability correction. Using survey data collected at two points from 324 undergraduate business students (166 students from the United States and 158 students from Singapore), the results of this within‐subject design study were mixed. Specifically, while social desirability inflated scores on personality measures, it also increased their criterion validity in Singapore. Additionally, self‐deception enhancement (SDE) predicted the inflation of openness to experience scores in the United States. Finally, in the sample from the United States, correcting for SDE increased the criterion validity of personality measures to a greater extent for those who scored high on horizontal individualism (HI) than it did for those who scored low on HI.